2021
DOI: 10.1016/j.rmed.2021.106453
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes and quality of life of COVID-19 survivors: A follow-up of 3 months post hospital discharge

Abstract: Background Over 66 million people worldwide have been diagnosed with COVID-19. Therefore, understanding their clinical evolution beyond hospital discharge is essential not only from an individual standpoint, but from a populational level. Objectives Our primary aim was to assess the impact of COVID-19 on health-related quality of life (HRQoL) 3 months after hospital discharge. Additionally, we screened for anxiety and depression and assessed important clinical outcomes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
72
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(108 citation statements)
references
References 27 publications
6
72
0
4
Order By: Relevance
“…A worsened quality of life is a fairly consistent finding for PACS [24,26,32,57,59,72,73]. In the absence of reference values for the SGRQ we could not define an overall worsened HrQoL, but data were consistent regarding their correlation with shortness of breath and fatigue, suggesting that we asked for important factors underlying the overall impairment in quality of life.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A worsened quality of life is a fairly consistent finding for PACS [24,26,32,57,59,72,73]. In the absence of reference values for the SGRQ we could not define an overall worsened HrQoL, but data were consistent regarding their correlation with shortness of breath and fatigue, suggesting that we asked for important factors underlying the overall impairment in quality of life.…”
Section: Discussionmentioning
confidence: 71%
“…Basic demographic characteristics and data on the hospital stay during COVID-19 of the 101 patients are given in Table 1A stratified according to sex. This stratification was chosen, as sex had turned out as major determinant of PACS in previous studies [57][58][59][60][61][62]. The median age was 60 (IQR 51-66; range 28-69) years, 58% of patients were male, 35% had a history of smoking, and 76% at least one comorbidity.…”
Section: Demographic Data Of the Clinically Examined Patientsmentioning
confidence: 99%
“…An analogous finding was mentioned in a study from Israel; patients requiring hospitalization with COVID-19 reported poor quality of life and needs prolonged medical follow up [ 26 ]. In addition to this, a Brazilian study highlighted that an ICU admission was an independent predictor of worsening health related quality of life [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Published June 10, 2020 , Sabes-Figuera et al, 2010 , Winston, 2020 , Xu et al, 2017 , Stroup et al, 2000 , Page et al, 2021 , Better systematic review management. Published June 11, 2020 , Stang, 2010 , Shuwa et al, 2021 , Sonnweber et al, 2021 , Taboada et al, 2021 , Todt et al, 2021 , Wong et al, 2020 , Zhou et al, 2021 , Ghosn et al, 2021 , Say et al, 2021 , Pilotto et al, 2021 , Liyanage-Don et al, 2021 , Miyazato et al, 20202020 , González et al, 2021 , Fernández-de-las-Peñas et al, 2021 , Fernández-de-Las-Peñas et al, 2021 , Arnold et al, 2021 , Fortini et al, 2021 , García-Abellán et al, 2021 , Ong et al, 20212021 , PHOSP-COVID Collaborative Group et al, 2021 , Skala et al, 2021 , Sykes et al, 2021 , Santis et al, 2020 , van den Borst et al, 2020 , Venturelli et al, 2021 , IL6 - Clinical: Interleukin 6, Plasma. Accessed June 26, 2021 , Elkan et al, 2021 , Frontera et al, 2021 , Garrigues et al, 2020 , Havervall et al, 2021 , Rogers et al, 2020 , Hoffman and Vilensky, 2017 , Komaroff and Lipkin, 2021 , Higgins et al, 2021 , Douaud et al, 2021 , Lee et al, 2021 , Guedj et al, 2021 , Libby and Lüscher, 2020 , Oronsky et al, 2021 , Yong, 2021 , Sartori et al, 2012 , Rosenblat et al, 2014 , Sonneville et al, 2009 , Gałecki et al, 2018 , Heckenberg et al, 2018 , Xiong et al, 2020 , Taquet et al, 2021 , McIntyre et al, 2019 , …”
Section: Uncited Referencesmentioning
confidence: 99%